Peran BASYARNAS dalam Penyelesaian Sengketa Ekonomi Syariah di Luar Pengadilan di Indonesia - Fildza Nazhifah Kamila; Saskia Mediana; Nazara Anisa; Elisabeth Julietha Roulina; Rafi Alfarisi (Media Hukum Indonesia (MHI), 2026)
The rapid growth of the Islamic economic sector in Indonesia has increased the potential for disputes arising from various Islamic business and financial transactions. Consequently, an effective dispute resolution mechanism that ensures legal certainty while adhering to Sharia principles is required. One of the institutions that plays a significant role in resolving Islamic economic disputes outside the court system is the National Sharia Arbitration Board (Badan Arbitrase Syariah Nasional/BASYARNAS). This study aims to examine the role of BASYARNAS in resolving Islamic economic disputes and to analyze the mechanisms and advantages of dispute settlement through this institution. The research employs a normative legal research method using both statutory and conceptual approaches. The data were collected through library research, including the examination of legislation, legal literature, academic journals, and other relevant sources. The findings indicate that BASYARNAS serves as an alternative dispute resolution institution that offers a process which is efficient, confidential, cost-effective, and consistent with Sharia principles. The dispute resolution mechanism through BASYARNAS involves the submission of an arbitration request, case examination, reconciliation efforts, evidentiary proceedings, and the issuance of an arbitration award that is final and binding. These advantages make BASYARNAS an effective option for Islamic business actors in resolving disputes outside the court system.